2015
DOI: 10.1177/1934578x1501000327
|View full text |Cite
|
Sign up to set email alerts
|

Dual Excitatory and Smooth Muscle-relaxing Effect of Sideritis montana Extract on Guinea-pig Ileum

Abstract: The neuronal and smooth muscle effects of a methanol extract prepared from the air-dried flowering aerial parts of Sideritis montana L. (SME) was tested in vitro on Guinea-pig ileum. The chemical composition of the investigated extract was analysed by HPLC-MS, and chrysoeriol, chlorogenic acid and caffeic acid were detected as main constituents. The isolated organ assay showed that S. montana extract caused an immediate contraction and a more slowly developing inhibitory response in the ileum. The SME-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
(36 reference statements)
0
5
0
2
Order By: Relevance
“…Chrysoeriol (luteolin 3 -methyl ether), a bioactive flavonoid, is found in several tropical, medicinal plants known for potent antioxidant [36], anti-inflammatory, antitumor, antimicrobial, and antiviral activity. In the literature, some reports show selective bronchodilator effect by K + -induced contractions in the trachea and aorta [37], as well as smooth muscle-relaxing effects [38]. No data to date are available regarding the question of whether 3,5,6,7,8,3 ,4 -heptamethoxyflavone inhibits contractility on uterine smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Chrysoeriol (luteolin 3 -methyl ether), a bioactive flavonoid, is found in several tropical, medicinal plants known for potent antioxidant [36], anti-inflammatory, antitumor, antimicrobial, and antiviral activity. In the literature, some reports show selective bronchodilator effect by K + -induced contractions in the trachea and aorta [37], as well as smooth muscle-relaxing effects [38]. No data to date are available regarding the question of whether 3,5,6,7,8,3 ,4 -heptamethoxyflavone inhibits contractility on uterine smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly used orally as tea for relieving cough associated with a cold, for reducing fever, against stomach ailments, as an antihysteric, tonic, and stimulant, and is used externally to treat wounds ( Table 2 ). The scientifically proven activities are antioxidant, antimicrobial, anti-inflammatory, smooth muscle-relaxing, anti-proliferative, and cytotoxic activities [ 17 , 24 , 25 , 26 , 27 , 28 , 29 ]. These results support the traditional use of S. montana for the healing and prevention of many diseases of modern times.…”
Section: Discussionmentioning
confidence: 99%
“…These results support the traditional use of S. montana for the healing and prevention of many diseases of modern times. Serbia: wound healing herb (aerial parts)/decoction, infusion/internally [9] Smooth muscle-relaxing methanol extract [27] Bulgaria: for relief of cough associated with cold ns [33] Antiproliferative (cervical cancer) and cytotoxic (melanoma, breast adenocarcinoma and human colon cancer) ethanol, methanol, hexane and ethyl acetate extracts, essential oil [17,22] Spain: digestive ns/infusion/internally [34] Antiinflammatory methanol extract [28] ns-not specified.…”
Section: Sideritis Montanamentioning
confidence: 99%
See 1 more Smart Citation
“…In our lab, we routinely check the phytochemicals and computationally design their newer derivatives which ultimately may become suitable candidates for the treatment of Alzheimer's disease and metabolic disorder like cancer. Earlier studies on caffeic acid showed its mild stimulant effect (Liszt, Eder, Wendelin, & Somoza, 2015;Shin et al, 2015;Toth et al, 2015). The past studies also showed its cytoprotective effect (Lee et al, 2015;Nunes et al, 2015), antiangiogenic effect, and moderate toxicity (Akyol et al, 2015;Kosova, Kurt, Olmez, Tuğlu, & Arı, 2015) that can be affected due to the stability of the compounds.…”
Section: Introductionmentioning
confidence: 99%